Electrochemical Synthesis, Structure Elucidation and Antibacterial Evaluation of 9a-aza-9a-chloro-9a-homoerythromycin A - Zoran Mandic; Gorjana Lazarevski; Zlatko Weitner; Predrag Novak; Nataša Maršić; Ana Budimir (International Association of Physical Chemists (IAPC), 2014)
Electrochemical synthesis, structure elucidation and antibacterial evaluation of 9a-aza-9a-chloro-9a-homoerythromycin A were carried out. It was found that the anodic oxidation of 9a-aza-9a-homoerythromycin A via electrogenerated reactive chlorine species leads to the chlorination of lactam nitrogen in high yield provided the pH of the reaction mixture is maintained above 3. NOESY spectra reveal the existence of the mixture of two conformational families in the solution, the "folding-out" conformer being slightly more abundant comparing to 9a-Aza-9a-homoerythromycin A. The chlorine substitution of lactam hydrogen resulted in improved antimicrobial potency against Sreptococcus pyogenes PSCB0542, Moraxella catarrhalis ATCC 25238, Haemophilus  influenzae ATCC 49247 and Enteroccocus faecalis ATCC 29212.